Balance of protein supplements according to the criterion of convertible protein - S. V. Zverev; M. A. Nikitina (Пищевые системы)
The main sources of vegetable protein are seeds of legumes and oilseeds, which differ as by total content as by the quality. One of the least expensive and most rapid method of assessing the quality of protein is a chemical method, based on a comparative analysis of its amino acid composition, in particular, essential amino acids (EAA), and "ideal" protein. A widespread indicator of the proximity of the protein to the ideal is the minimum period, which shows how much of it can be used by the body for plastic needs (the main exchange and ensuring of body weight gain). Obviously, the more of this (convertible) protein in the product, the better (but not more than the daily value). One of the methods of obtaining a grain product with an increased convertible protein is blending, i.e. mixing in a certain proportion of different types of protein raw materials. In this case, the content of the converted mixture may be greater than in the components, and the excess less. The article presents a methodology for calculating the proportion of convertible protein in the product, as well as a new approach to the formation of effective mixtures. On the basis of this method, the results of the calculation of such mixtures on the example of a grain product with the use of collapsed white lupine, linseed cake and ginger seeds as components are shown. In all cases, there are rational proportions of the mixture, in which its convertible protein exceeds this figure in the component. The accuracy of the calculations largely depends on the accuracy of the total protein content and EAA.